PENGEMBANGAN COMPUTER BASED TESTING MENGGUNAKAN APLIKASI KAHOOT! UNTUK EVALUASI PEMBELAJARAN - Iskandar, M. Yakub; Aisyah, Siti; Novrianti, Novrianti (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
The problem with evaluating learning outcomes using paper-based tests is that the scoring calculation process takes a long time. So, the test results cannot be known directly. The implementation of learning outcomes evaluation in learning evaluation courses so far still uses paper-based tests, so students have to wait to find out the test results. This research and development apply the ADDIE model which is carried out in five stages. The instruments used in this research were tests and student response questionnaires regarding the use of the "Kahoot!" application. Analysis of the data obtained is divided into two types, namely quantitative data and qualitative data. The qualitative data results are based on criticism and suggestions presented by the validator to improve the question instrument. The results of the validation of the question instrument were in the "suitable for use with many revisions" category, the test results obtained 46 "valid" questions. Furthermore, the practicality test results are in the "quite practical" category with a score of 3.80 and for the effectiveness test results Asymp. Sig. (2-tailed) 0.068 means "there is no effect between tests using the "Kahoot!" by testing using Google Form”. However, judging from the test results obtained by students with different treatments, there are differences in scores, so this proves that this application is effective to use with very supportive signal provider requirements.